Importance and impacts of intermediary boundary organizations in facilitating payment for environmental services in Vietnam - Pham Thu Thuy; Campbell, Bruce M.; Garnett, S.T.; Aslin, H.; Hoang, M.H. (2010)
Intermediaries are seen as important actors in facilitating payments for environmental services (PES). However, few data exist on the adequacy of the services provided by intermediaries and the impacts of their interventions. Using four PES case studies in Vietnam, this paper analyses the roles of government agencies, non-government organizations, international agencies, local organizations and professional consulting firms as PES intermediaries. The findings indicate that these intermediaries are essential in supporting PES establishment. Their roles are as service and information providers, mediators, arbitrators, equalizers, representatives, watchdogs, developers of standards and bridge builders. Concerns have been raised about the quality of intermediaries’ participatory work, political influence on intermediaries’ activities and the neutral status of intermediaries. Although local organizations are strongly driven by the government, they are important channels for the poor to express their opinions. However, to act as environmental services (ES) sellers, local organizations need to overcome numerous challenges, particularly related to capacity for monitoring ES and enforcement of contracts. Relationships amongst intermediaries are complex and should be carefully examined by PES stakeholders to avoid negative impact on the poor. Each of the intermediaries may operate at a different level and can have different functions but a multi-sector approach is required for an effective PES implementation